Method for evaluating the importance of power grid nodes based on PageRank algorithm. Issue 11 (1st November 2014) - Li, Canbing; Liu, Wencan; Cao, Yijia; Chen, Hao; Fang, Baling; Zhang, Wei; Shi, Haiqing
Abstract : Cascading failures can easily occur and cause a major blackout in power grid when an important node breaks down. It is an essential problem to evaluate the importance of nodes in power system planning and operation. In this study, a method for evaluating the importance of power grid nodes based on PageRank (PR) algorithm is proposed. First, according to the comparison of the internet and power grid topology, a directed graph is established. Second, based on the directed graph, an index is proposed to estimate the importance of power grid nodes based on PR algorithm. Then, according to the characteristics of power grid, a modified algorithm, which takes the importance of nodal load, nodal load capacity and network topology into account, is proposed. Finally, case study shows the necessity of considering the factors to evaluate the importance of power grid nodes and the effective of index and algorithm to identify critical nodes in this study.